Predator - Cornwell, Patricia Dan (New York : G.P. Putnam's Sons, 2005)
Investigating the disappearance of two sisters in Florida, Dr. Kay Scarpetta follows clues that twist and turn, leading her into the psychopathic depths of a jailed serial killer's mind.
94481
Keywords: Scarpetta, Kay (Fictitious character); Forensic pathologists; Women physicians; Florida; Large type books; Mystery fiction